Characterization of an x‐ray tube‐based ultrahigh dose‐rate system for in vitro irradiations. Issue 11 (25th September 2021) - Cecchi, Daniel D.; Therriault‐Proulx, François; Lambert‐Girard, Simon; Hart, Alexander; Macdonald, Andrew; Pfleger, Mike; Lenckowski, Mark; Bazalova‐Carter, Magdalena
Abstract: Purpose: To present an x‐ray tube system capable of in vitro ultrahigh dose‐rate (UHDR) irradiation of small < 0.3 mm samples and to characterize it by means of a plastic scintillation detector (PSD). Methods and materials: A conventional x‐ray tube was modified for the delivery of short UHDR irradiations. A beam shutter system with a sample holder was designed and installed in a close proximity of an x‐ray tube window to enable <1 s irradiations at UHDR. The dosimetry was performed with a small 0.5‐mm long 0.5‐mm in diameter PSD irradiated with 80, 100, and 120 kVp beams and beam currents of 1–37.5 mA. The PSD signal was recorded at frame rates of 20 and 50 fps for shutter exposure between 100 and 1125 ms. Irradiation reproducibility was studied with the PSD. The x‐ray tube irradiation setup was modeled with Monte Carlo (MC) and dose on a surface of a phantom was also measured with films. The effect of dose delivery uncertainty to 300‐μm spheroids due to positioning and spheroid size was evaluated. Results: MC simulations showed good agreement with PSD measurements acquired at both frame rates of 20 and 50 fps in terms of beam temporal profile. PSD‐measured dose exhibited excellent linearity as a function of instantaneous dose rate from 3.1 to 118.0 Gy/s as well as shutter exposure time from 100 and 1125 ms for all investigated beam energies. PSD absorbed dose for the 80, 100, and 120 kVp beams agreed with MC simulations to within 5%. The total delivered doses ranged from 0.4 Gy for a 1‐mA, 80 kVp beam, and 100 ms shutter exposure to 166.9 Gy for a 37.5‐mA, 80 kVp beam, and a 1125 ms exposure. PSD irradiation reproducibility was < 0.5%. Simulated and measured dose fall off agreed and it was steep along the axis of the shutter slit (1%/0.1 mm) and with depth (2%/0.1 mm at 1‐mm depth). Spheroid positioning uncertainty of 300 μm resulted in dose difference of < 3% for x and y shifts but up to 7% uncertainty for a z‐shift parallel to the beam axis. A 16% difference in spheroid size resulted in <5% dose difference in spheroid absorbed dose. Conclusions: We have presented a cost‐effective x‐ray tube‐based system with a beam shutter designed for in vitro UHDR delivery and reaching dose rates of up to 118.0 Gy/s. The described shutter system can be easily implemented at other institutions, which might enable new researchers to investigate the radiobiology of UHDR irradiations in vitro.